Cellular Potts Models - Scianna, Marco; Preziosi, Luigi (Chapman & Hall/CRC mathematical and computational biology series, 2013)
A flexible, cell-level, and lattice-based technique, the cellular Potts model accurately describes the phenomenological mechanisms involved in many biological processes. Cellular Potts Models: Multiscale Extensions and Biological Applications gives an interdisciplinary, accessible treatment of these models, from the original methodologies to the la.